Organizational Communication : approaches and processes - Millar, Katherine (United States of America : Thomson Wadsworth, 2006)
Thomson Wadsworth se compromete a proporcionarle las soluciones de aprendizaje más contemporáneas en el campo de los estudios de comunicación. Ese compromiso se aplica a los conceptos que aprendes en el aula y las habilidades reales que llevas contigo. En Thomson Wadsworth, sabemos que los estudiantes de hoy serán los profesionales del mañana, y agradecemos la oportunidad de asociarnos con usted en su viaje hacia el aprendizaje permanente ... en cada paso del camino. Thomson Wadsworth is committed to providing you with the most contemporary learning solutions in the field of communication studies. That commitment applies to the concepts you learn in the classroom and the real skills you carry away with you. At Thomson Wadsworth, we knou that the students of today will be the professionals of tomorrow, and we welcome the opportunity to partner with you on your journey to lifelong learnnig... every step of the way.
BRIEF CONTENTS PART A FOUNDING APPROACHES PART B CONTEMPORARY APPROACHES PART C ENDURING PROCESSES PART D EMERGING PROCESSES
It includes subject Index It includes name Index
It includes references
Keywords: COMUNICACIÓN ORGANIZACIONAL